2014
DOI: 10.1039/c4ta01264j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning oxygen content and distribution by substitution at Co site in 112 YBaCo2O5+δ: impact on transport and thermal expansion properties

Abstract: Polycrystalline “112” ordered oxygen deficient double perovskites YBaCo2−xMexO5+δ (Me = Fe, Cu, Ni) were synthesized by a glycerol-nitrate route with 0.0 ≤ x ≤ 0.7 for Me = Fe, 0.0 ≤ x ≤ 0.6 for Me = Cu and x = 0.1 for Me = Ni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…One can see that copper substitution results in the increase of the elementary unit size. This change reflects replacement of Co 3+ for larger Cu 2+ cations [35], and is consistent with recent data on copper substituted barium yttrium double perovskite cobaltite [36]. The other effect of copper doping is related to the decrease in oxygen content (5 + δ) in the as-prepared samples from 5.77 to 5.52 for x = 0 and 0.5, respectively.…”
Section: Resultssupporting
confidence: 86%
“…One can see that copper substitution results in the increase of the elementary unit size. This change reflects replacement of Co 3+ for larger Cu 2+ cations [35], and is consistent with recent data on copper substituted barium yttrium double perovskite cobaltite [36]. The other effect of copper doping is related to the decrease in oxygen content (5 + δ) in the as-prepared samples from 5.77 to 5.52 for x = 0 and 0.5, respectively.…”
Section: Resultssupporting
confidence: 86%
“…Such good transport properties results from highly-effective electron transfer occurring through the mentioned Zener mechanism [11,36]. It is generally known that substitution of cobalt with different 3d metals (such as iron or manganese) has generally negative impact on the total conductivity [35,37]. This behaviour can be explained taking the considered ReBaCo2-xMnxO5+δ group of materials as an example.…”
Section: Perovskite-type Cathode Materials: Selected Issues Regardingmentioning
confidence: 99%
“…A partial substitution of cobalt in Ln BaCo 2 O 5+δ perovskites by low-valence Ni- [ 129 , 130 , 131 ], Zn- [ 132 ], or Cu- [ 86 , 131 , 133 , 134 , 135 ] ions led to a slight increase intheir lattice constants [ 131 ] and a decrease in oxygen content (δ) [ 131 , 132 ], TEC [ 129 , 130 , 134 , 135 ], and electrical conductivity values [ 86 , 129 , 130 , 131 , 134 ]. In some cases, such a substitution improved the electrochemical performance of the derived cathode materials [ 129 , 130 , 132 , 134 ].…”
Section: Electrochemical Performance Of Layered Oxygen-deficient Perovskitesmentioning
confidence: 99%
“…The effect of the partial substitution of cobalt with iron in layered perovskites of REE and barium and their A-site-deficient and A-site-substituted derivatives was intensively studied in a number of works [ 86 , 131 , 135 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ]. It was found that Fe-doping results in an increase of lattice constants [ 131 , 143 , 144 , 145 , 147 , 148 , 151 , 153 , 154 , 157 ] and oxygen contents [ 131 , 146 ]. Electrical conductivity of such Fe-doped cobaltites decreases with Fe-doping [ 143 , 145 , 146 , 147 , 153 , 154 , 157 ].…”
Section: Electrochemical Performance Of Layered Oxygen-deficient Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation